Monitoring 7Be and tritium in rainwater in Daejeon, Korea and its significance. (March 2016) - Kim, K.J.; Choi, Y.; Yoon, Y.-Y.
Abstract: We investigated the concentrations of beryllium-7 and tritium in rainwater along with sodium concentration in the region of Daejeon, Korea for 7 months. The results demonstrate that 7 Be in rainwater is inversely proportional to the amount of sodium present and proportional to the rainfall. Also, it was observed that tritium reaches ground level about a month later than 7 Be. This study will guide prospective geological research applications associated with cosmogenic nuclides especially in rainwater for the Korean region. Highlights: New data set of both Be-7 and H-3 in rainwater of Korea. New data set of cosmogenic nuclides and elemental concentration in rainwater. Cosmogenic nuclide variation of rainwater with respect to the atmospheric condition. Elemental concentration in rainwater as local atmospheric source.